Physical protection regulates microbial thermal responses to chronic soil warming. (August 2021) - Liu, Xiao Jun Allen; Frey, Serita D.; Melillo, Jerry M.; DeAngelis, Kristen M.
Abstract: Climate warming can affect the temperature sensitivity of microbial activity and growth efficiency, possibly explained by changes to microbially unavailable carbon (C) protected within in soil aggregates. We assessed physical protection by crushing macroaggregates (250–2000 μm) and microaggregates (<250 μm) isolated from mineral soils exposed to 27 years of experimental warming (+5 °C). We hypothesized that removal of physical protection would increase microbial activity and reduce C use efficiency (CUE). We found that crushing increased microbial respiration and biomass turnover rate, but did not affect CUE. We also hypothesized that long-term warming would reduce the effect of physical protection on microbial activity, and that physical protection would attenuate microbial temperature sensitivity in heated compared to control soils. We found that long-term warming was associated with a smaller effect of physical protection for microbial respiration but with a larger effect for biomass turnover rate in macroaggregates. Physical protection reduced the temperature sensitivity of respiration but enhanced the temperature sensitivity of microbial biomass turnover rate in heated compared to control soils. Our work shows that long-term warming has contrasting effects on how microbial respiration, biomass turnover rate, and their thermal responses are mediated by physical protection within soil aggregates. Highlights: Physical protection effects were tested by crushing aggregates isolated from soils. Long-term warming increased the physical protection effect on microbial turnover rate. Long-term warming did not affect the carbon use efficiency of protected soil carbon. Long-term warming altered microbial temperature sensitivity of protected carbon.